IMPACT OF FINANCIAL REFORMS IN IRRIGATION SECTOR OF PUNJAB, PAKISTAN - I. A. Baig; M. Ashfaq; S. Hassan; K. Mushtaq (Journal of Animal and Plant Sciences, 2008)
Pakistan has the world's largest contiguous irrigation system which was designed to provide uninterrupted supplies of irrigation water during the entire year. It has been observed that system has lost its efficiency over time. In this scenario a comprehensive reform program has been introduced in the irrigation sector. Basic aim of the whole reform program is to delegate the system to the ultimate users so that they can efficiently manage/maintain it and thus ultimately increasing the water productivity and reducing poverty. Present study was aimed to analyze the effectiveness of these reforms, which were carried out in Lower Chanab Canal (East) irrigation circle in Punjab (covering almost 1.8 million hectares of irrigated land) as a pilot project. In order to assess the different relationships between irrigation reforms, cost recovery, improved infrastructure, system efficiency, head-tail equity and ultimately the productivity and income of the farmers, a comprehensive survey of the area was carried out. Data were collected in the study area through comprehensive field survey for the two periods i.e. pre-reform period and post-reform period (year 2002-03 to 2006-07) from the same set of sampling units. Effectiveness of reform process was judged through the comparison of established parameters and econometric analysis of the data. Results of the study were largely supporting the notion of irrigation reforms. It was estimated that irrigation charges recovery has improved with an over all improvement in the O&M of the system. Sustainability indicators and water delivery indicators have also shown improvement in the post reform period thus increasing the productivity level.
Keywords: Impact assessment; Irrigation reforms; IMT; Pakistan